Dysregulation of anti-tumor immunity by the matrix metalloproteinase-2 - Godefroy, Emmanuelle (Landes Bioscience, 2012)
The matrix metalloproteinase-2 (MMP-2), overexpressed in most cancers, induces TH2 polarization by conditioning dendritic cells to over-express OX40L and downregulate IL-12p70 through the degradation of the type-I IFN receptor IFNAR1. Elucidating mechanisms underlying detrimental tumor-associated type-2 responses represent a crucial step in designing effective immune therapies to treat cancer patients.